SUSTAINABLE SUPPLY CHAIN PRACTICES THAT DRIVE BOTTOM - LINE GROWTH - Iroda Danabayeva Uktam kizi (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This comprehensive analysis examines how sustainable supply chain practices have evolved from environmental initiatives to strategic business drivers that deliver measurable financial returns. The article demonstrates that companies implementing sustainable supply chain strategies achieve average cost reductions of 15-25% while enhancing brand reputation and competitive positioning. Key sustainable practices explored include energy efficiency optimization, waste reduction through circular economy models, supply chain optimization with local sourcing, and water conservation management. The research highlights technology enablers such as digital twin technology, blockchain transparency systems, and IoT sensors that amplify sustainability benefits. The article provides practical implementation strategies emphasizing quick wins, measurement protocols, and stakeholder engagement to maximize both environmental impact and bottom-line growth. Evidence shows that sustainable practices provide crucial risk mitigation against climate change, resource scarcity, and regulatory pressures while creating long-term competitive advantages for early adopters.